Curriculum Development and Educational Practices for Islamic Education: An Analysis of the Merdeka Curriculum at Integrated Islamic Junior High School in Indonesia - Mundiatul Mila; Muhammad Zuhdi (KURAS Institute, 2025)
The implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) at Integrated Islamic Junior High School SMPIT Al Haraki still encounters several challenges, particularly in maintaining consistent execution, teachers’ readiness to adapt learning modules, and disparities in students’ digital literacy. This study aims to analyze how the curriculum is developed, implemented, and evaluated within the context of an integrated Islamic school. A qualitative descriptive method was employed, using interviews, observations, and document analysis involving PAI teachers, school leaders, and students. The findings reveal that curriculum development follows a grass-roots model positioning teachers as the primary drivers, supported by philosophical, religious, sociological, psychological, and scientific foundations. Its implementation integrates religious habituation with digital technology using Chromebooks, Google Workspace, and interactive applications such as Quizizz, Wordwall, and Padlet. Evaluation is conducted holistically through academic assessments, moral observations, and tahfiz achievement tracking. The main challenges involve students’ concentration, classroom conditions, and variations in digital competencies. This study contributes by offering an integrative model of PAI curriculum evaluation that combines academic, spiritual, and character dimensions, while also providing practical insights for other schools aiming to develop an adaptive and Islamic-oriented Merdeka Curriculum.